Evaluating Indonesian Islamic Financial Technology Scholarly Publications: A Bibliometric Analysis - Sofyan, Syaakir; Nursyamsu, Nursyamsu; Sofyan, A. Syathir; Mansyur, Abdurrahman; Aisya, Sitti; Noval, Noval; Nurfitriani, Nurfitriani (Universitas Islam Negeri Raden Intan Lampung, 2022)
This study aims to examine the development of trends in Islamic fintech studies published in journals under the SINTA category. This paper uses the bibliometric method with Harzing's Publish or Perish analysis tools to collect 121 article metadata on Google Scholar and R Studio and VOSviewer to analyze bibliographic data obtained automatically. The results show that the number of publications on Islamic fintech has increased significantly. The results of the bibliometric analysis found that the authors tend to use the term